Assessing the physical, mechanical properties, and γ-ray attenuation of heavy density concrete for radiation shielding purposes. Issue 2 (4th March 2019) - Ouda, Ahmed S.; Abdelgader, Hakim S.
Abstract: The main purpose of this research is to improve the shielding of gamma rays by developing special concrete with high physico-mechanical properties using local aggregates. Various concrete mixtures are designed using heavy fine aggregate as a substitute for normal fine aggregate at rates of 20, 40, 60, 80, and 100%, by weight. Other concrete mixtures have been designed by replacing coarse aggregate with 50 and 60% of heavy fine aggregate. The properties such as density, compressive strength, and tensile strength of hardened mixtures were studied. Gamma ray attenuation has been studied on concrete mixtures after exposure to utilized radiation source comprised 137 Cs radioactive element with photon energy of 0.662 MeV. From the results, we concluded that the density and compressive strength in addition to the linear attenuation coefficient of hardened mixtures increased with the ratio of replacing normal aggregate with heavy aggregate up to 60%. With an increase of the ratio more than 60%, compressive strength and tensile strength were reduced with the continued increase in density. On the other hand, density and the linear attenuation coefficient increased with the replacement of coarse aggregate by 50 and 60% of the heavy fine aggregate; while both compressive strength and tensile strength decreased.